8,14-Secogammacera-7,14(27)-diene-3,21-dione–8,14-secogammacera-7,14-diene-3,21-dione (1.5/0.5) from the bark of Lansium domesticum Corr. - Roekmi-ati Tjokronegero; Tri Mayanti; Unang Supratman; Mat Ropi Mukhtar; Seik Weng Ng (Acta Crystallographica Section E, 2009)
The components of the title cocrystal, 1.5C30H40O2·0.5C30H40O2, each have two tetrahydrodecalin-type fused rings connected through an ethylene fragment [R—CH2—CH2—R′ torsion angles: 158.1 (7) ° in the major component and 157.5 (6)° in the minor component]. The structure is a non-merohedral twin, with a minor twin component of 26%. The exocyclic double-bonded C atom of the major component of the cocrystal is disordered over two sites of equal occupancy.